Review and Hypothesis: A Potential Common Link Between Glial Cells, Calcium Changes, Modulation of Synaptic Transmission, Spreading Depression, Migraine, and Epilepsy—H+ - Malchow, Robert Paul; Tchernookova, Boriana K.; Choi, Ji-in Vivien; Smith, Peter J. S.; Kramer, Richard H.; Kreitzer, Matthew A. (Frontiers in Cellular Neuroscience, 2021)
There is significant evidence to support the notion that glial cells can modulate the strength of synaptic connections between nerve cells, and it has further been suggested that alterations in intracellular calcium are likely to play a key role in this process. However, the molecular mechanism(s) underlying glial cell-mediated alterations between neurons remains contentiously debated. Recent experiments have suggested that alterations in extracellular H+ efflux initiated by extracellular ATP may play a key role in the modulation of synaptic strength by radial glial cells in the retina and astrocytes throughout the brain. ATP-elicited alterations in H+ flux from radial glial cells were first detected from Müller cells enzymatically dissociated from the retina of tiger salamander using self-referencing H+-selective microelectrodes. The ATP-elicited alteration in H+ efflux was further found to be highly evolutionarily conserved, extending from Müller cells isolated from species as diverse as lamprey, skate, rat, mouse, monkey and human. More recently, self-referencing H+ electrodes have been used to detect ATP-elicited alterations in H+ efflux around individual mammalian astrocytes from cortex and hippocampus. Tied to increases in intracellular calcium, these ATP-induced extracellular acidifications are well positioned to be key mediators of synaptic modulation. In this article, we examine evidence supporting H+ as a key modulator of neurotransmission, review data showing that extracellular ATP elicits an increase in H+ efflux from glial cells, and describe the potential signal transduction pathways involved in glial cell – mediated H+ efflux. We then examine the potential role that extracellular H+ released by glia might play in regulating synaptic transmission within the vertebrate retina, and then expand the focus to discuss potential roles in spreading depression, migraine, epilepsy, and alterations in brain rhythms, and suggest that alterations in extracellular H+ may be a unifying feature linking these disparate phenomena.